(untitled) (Asian Journal of Medical and Biological Research, 2016)
Oomycetes, also known as water molds, can cause serious infection to plants and animals especially at lower temperature although they dwell in freshwater and moist ecosystem throughout the year. The aim of this research was to investigate the diversity of oomycetes inhabiting in small water bodies during summer. Three types of samples i.e. water, fish mucus and apparently infected muscle samples of fish were collected from a large fish farm consisting of over 100 medium to large ponds in Mymensingh during summer (March to June) in 2015. A total number of 385 samples (284 of water, 79 of mucus and 22 of apparently infected muscle samples) were collected in 15 ml sterile falcon tubes with baits in each. Eleven of the isolates were isolated in Potato Dextrose Agar (PDA) plates and were identified using molecular methods that included DNA extraction, PCR amplification and subsequent sequencing of the ITS region of the genomic DNA of the samples. BLAST analysis to GenBank revealed that two of the isolates were 99% similar to Pythium sp. (HQ643814), three of the isolates were 98-99% similar to Pythium sp. (KT247392), and each of the remaining four isolates was similar up to 99% to Pythium sp. (KF836354), 99% to Pythium sp. (EU544193), 99% to Pythium rhizo-oryzae (HQ643757) and 100% to Pythium catenulatum (KP862946). Two of the eleven isolates were not assessed due to sequencing error. Phylogenetic analysis revealed that six of the isolates are of clade B1 and three of the isolates are of clade B2 in the Pythium phylogeny. The results partially suggest that plant pathogenic oomycetes are more common in summer than animal or fish pathogenic isolates in the sampled farm however; intensive sampling with a broad range of freshwater ecosystems during summer can give a clearer view on oomycete diversity in Bangladesh. Asian J. Med. Biol. Res. June 2016, 2(2): 236-246